Uterine hypertonia and nuchal cord causing severe fetal bradycardia in a parturient receiving combined spinal-epidural analgesia during labor: Case report and review of literature - Uma Srivastava; Komal Joshi; Amrita Gupta; Yogita Dwivedi; Saroj Singh (Wolters Kluwer Medknow Publications, 2012)
Fetal bradycardia is common following spinal opioids administered for pain relief during labor. This slowing is usually benign and short lived. Although it leads to some anxiety among obstetricians and anesthesiologists, it rarely results in urgent operative delivery. Here, we are reporting a case where urgent caesarean delivery was needed due to severe and persistent fetal bradycardia following low-dose intrathecal fentanyl. Fetal bradycardia possibly was due to hypertonic uterine contractions complicated by tightly wrapped cord round the neck.